Evolving research on periodontal health of abutment teeth in removable partial dentures: A Scopus-based bibliometric analysis - Nor Faharina Abdul Hamid; Farha Ariffin; Fara Azwin Adam; Solehuddin Shuib; Rohana Ahmad (Journal of Indian Society of Periodontology)
With partial edentulism prevalent among aging populations retaining natural teeth, understanding the relationship between removable partial dentures (RPDs) and abutment teeth periodontal health is crucial. To provide a bibliometric analysis of research trends on periodontal considerations of abutment teeth in RPDs, highlighting key publications, research clusters, and influential keywords from 1948 to 2024. An advanced search of Elsevier’s Scopus database was conducted, extracting data such as publication titles, years, citations, journals, countries, and keywords. Bibliometric analysis and network visualizations were generated using Biblioshiny and VOSviewer software. The annual growth rate of studies on periodontal consideration of abutment teeth in RPDs was 2.39%. The Journal of Prosthetic Dentistry had the most publications and citations, while the Journal of Periodontology held the highest average and normalized citations, signifying its impact. Highly cited articles were predominantly clinical studies. Coauthorship analysis showed that the United States, Japan, and Germany had the highest research output, while Sweden, Switzerland, and Germany led in average citations per document, highlighting Europe’s strong influence in this research area. The VOSviewer map identified nine distinct research clusters covering various aspects of prosthodontics, including material innovations, prosthetic design, patient quality of life, clinical assessments, complications, and advanced technologies. High-impact terms included “longitudinal study,” “crowns,” and “Periotest value” based on average citations, while “PEEK” leads in average normalized citations, indicating its growing influence. Periodontal considerations are central to research on abutment teeth in RPDs, highlighting the need for comprehensive, long-term evaluations of periodontal health and abutment tooth stability.